Zur Frage der jungen Gewannfluren - Vogt, Jean (ERDKUNDE, 1953)
After some general remarks regarding the interpretation of the field patterns as depicted by early cadastral maps, it is pointed out how Gewannfluren (’open-fields’) emerged quite suddenly not so long ago. The farming of a tract of land by as few as two holders may result in a systematic cutting up of the land into a disproportionately large number of strips. The strips of the owners or tenants change always in the same pattern between each other; the place of Schläge (Schlag = a parcel of strips put under the same crop) may even be taken by proper Zeigen (Zeige = ’field’, as in the threefield system). Situations of this kind are to be found in parishes of the Rheinpfalz (Rhenish Palatinate) where, after the warfare of the 17th century, the land was split up into a great number of strips among a very few shareholders. From this point onwards the Gewannflur is firmly established. The technological and psychological reasons of this practice are not discussed at this stage.